Longitudinal Effects of SafeTalk, a Motivational Interviewing-Based Program to Improve Safer Sex Practices Among People Living with HIV/AIDS - Golin, Carol E. (2012)
Programs to help people living with HIV/AIDS practice safer sex are needed to prevent transmission of HIV and other sexually transmitted infections. We sought to assess the impact of SafeTalk, a multicomponent motivational interviewing-based safer sex program, on HIV-infected patients’ risky sexual behavior. We enrolled sexually active adult HIV-infected patients from one of three clinical sites in North Carolina and randomized them to receive the 4-session SafeTalk intervention versus a hearthealthy attention-control. There was no significant difference in the proportion of people having unprotected sex between the two arms at enrollment. SafeTalk significantly reduced the number of unprotected sex acts with at-risk partners from baseline, while in controls the number of unprotected sex acts increased. Motivational interviewing can provide an effective, flexible prevention intervention for a heterogeneous group of people living with HIV.